2007
DOI: 10.1302/0301-620x.89b12.18969
|View full text |Cite
|
Sign up to set email alerts
|

Medium- and long-term performance of 11 516 uncemented primary femoral stems from the Norwegian arthroplasty register

Abstract: Primary uncemented femoral stems reported to the Norwegian arthroplasty register between 1987 and 2005 were included in this prospective observational study. There were 11 516 hips (9679 patients) and 14 different designs of stem. Kaplan-Meier survival probabilities and Cox regression were used to analyse the data. With aseptic loosening as the end-point, all currently used designs performed excellently with survival of 96% to 100% at ten years. With the end-point as stem revision for any cause, the long-term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
94
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(106 citation statements)
references
References 36 publications
10
94
0
2
Order By: Relevance
“…It is important to note that in our study using an uncemented stem, we found young age and male sex were not associated with a higher risk of aseptic stem loosening into the early third decade. Our results partially confirm the findings of Hallan et al, who found no influence of age at surgery on the survival of uncemented stems in a registry analysis [25]. In contrast to our findings, male sex had a moderate negative influence on long-term stem survival (relative risk 1.3) in their registry study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is important to note that in our study using an uncemented stem, we found young age and male sex were not associated with a higher risk of aseptic stem loosening into the early third decade. Our results partially confirm the findings of Hallan et al, who found no influence of age at surgery on the survival of uncemented stems in a registry analysis [25]. In contrast to our findings, male sex had a moderate negative influence on long-term stem survival (relative risk 1.3) in their registry study.…”
Section: Discussionsupporting
confidence: 90%
“…There are a variety of uncemented stems that have been associated with excellent mid-term clinical and radiographic outcomes, whereas others showed disappointing results [25,30]. However, there are few reports on the survival of uncemented stems with a minimum followup of 20 years or more [1,5,36,39].…”
Section: Introductionmentioning
confidence: 99%
“…Thirty-six surgeons performed a median of five operations each (range, [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Patients underwent a bipolar hemiarthroplasty with either a cemented femoral stem (Spectron; Smith & Nephew, Memphis, TN, USA) (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The purpose of this two-center randomized equivalence trial was to compare a hemiarthroplasty using a well-documented cemented femoral stem [7,12] with a hemiarthroplasty using a well-documented hydroxyapatitecoated proximal press-fit uncemented implant [9,23,26]. When we evaluated results of this trial at 1 year, we found comparable outcomes between the two groups for all outcome measures studied [5], and, specifically, the mean Harris hip score was equivalent between the groups at 3 months and 1 year; the duration of surgery and intraoperative blood loss were less in the uncemented group (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this two-center randomized equivalence trial was to compare a hemiarthroplasty using a well-documented cemented implant [13,19] (Fig. 1) with a hemiarthroplasty using a well-documented HA-coated proximal press-fit uncemented implant [16,35] (Fig. 2), with the following three research aims: (1) Will any differences in intraoperative events be detectable?…”
Section: Introductionmentioning
confidence: 99%